A Review of Treatment Methods and Available Therapies for Individuals with ADHD - Gałuszka, Zuzanna; Papachristoforou, Natalie; Michałka, Daria; Makar, Monika; Bartuś, Tomasz; Góra, Żaneta; Bąk, Emilia; Głowacka, Justyna; Kocjan, Aleksandra; Chmiel, Radosław (Quality in Sport, 2025)
This review explores treatment approaches and therapies for Attention Deficit Hyperactivity Disorder (ADHD), a neurodevelopmental condition affecting adults, with symptoms often persisting from childhood into adulthood. The research examines the efficacy, tolerability, and accessibility of pharmacological and psychosocial interventions. ADHD management necessitates a multimodal approach combining medications, behavioral therapies, and educational interventions tailored to individual needs. The analysis focuses on stimulant and non-stimulant medications, including methylphenidate, amphetamines, atomoxetine, and alpha-2 agonists, with regional variations in treatment guidelines. Stimulants, primarily methylphenidate and amphetamine formulations, demonstrate robust efficacy in symptom reduction for patients. Non-stimulant options like atomoxetine are recommended for patients with contraindications to stimulants. Emerging formulations, such as extended-release medications, address tolerance and adherence challenges. Psychosocial interventions, particularly cognitive behavioral therapy (CBT), complement pharmacological treatments by targeting organizational skills, emotional regulation, and comorbidities like anxiety and depression. Evidence suggests that combined approaches improve long-term functional outcomes, such as academic performance and interpersonal relationships. Despite advances, gaps in treatment access and the need for individualized care remain significant challenges. This review underscores the importance of ongoing research to optimize ADHD management strategies and ensure equitable access to effective therapies worldwide.